A novel strategy for preparation of α′ + β Dual-phase microstructure through heating massive-like transformation induced by Electropulsing in Ti-6Al-4V Alloy. (February 2023) - Zhou, Yachong; Xu, Xiaofeng; Zhao, Yang; Yan, Xudong; Wu, Chao; Hou, Qingyu; Wei, Lai
Abstract: A novel dual-phase microstructure (α′ + β) has been prepared in Ti-6Al-4V alloy, which breaks the trade-off effect between strength and plasticity during the traditional solution treatment. This result is attributed to the rapid heating-induced massive-like transformation (α + β → βm ) via electropulsing treatment and following martensitic transformation (βm  → α′ + β) by water quenching. It was found that there was almost no alloy elements diffusion during the whole transition. Therefore, different from the traditional solution treatment product of V-supersaturated α′, the Al-enriched α′ and remained β were obtained. Graphical Abstract: Image, graphical abstract